2021
DOI: 10.3233/jad-201216
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Deficits in Motor, Sensory, and Olfactory Domains in Dementia

Abstract: Background: There exist functional deficits in motor, sensory, and olfactory abilities in dementias. Measures of these deficits have been discussed as potential clinical markers. Objective: We measured the deficit of motor, sensory, and olfactory functions on both the left and right body side, to study potential body lateralizations. Methods: This IRB-approved study (N = 84) performed left/right clinical tests of gross motor (dynamometer test), sensory (Von Frey test), and olfactory (peppermint oil test) abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…On the other hand, MCI patients performed similarly to control subjects on visual recognition memory tests (Delayed Matching to Sample, Pattern Recognition Memory, and Spatial Working Memory) (Barbeau et al, 2004). Interestingly, the present study indicated that aMCI is not only accompanied by memory dysfunctions but also by a functional deficit in motor abilities (as assessed with the Motor Screening Task), which is a feature of dementia (Schonfeld et al, 2021).…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, MCI patients performed similarly to control subjects on visual recognition memory tests (Delayed Matching to Sample, Pattern Recognition Memory, and Spatial Working Memory) (Barbeau et al, 2004). Interestingly, the present study indicated that aMCI is not only accompanied by memory dysfunctions but also by a functional deficit in motor abilities (as assessed with the Motor Screening Task), which is a feature of dementia (Schonfeld et al, 2021).…”
Section: Discussionmentioning
confidence: 52%
“…Hemispheric lateralization is a widely accepted organizational principle of the human brain. Brain lateralization was associated with neurodevelopment [ 93 , 94 ], aging [ 95 , 96 ], cognition [ 97 , 98 ], emotion [ 99 , 100 ], and neuropsychiatric disorders, such as schizophrenia [ 101 , 102 ], depression [ 103 , 104 ], dementia [ 105 ], Alzheimer’s disease [ 96 , 106 ] and PD [ 107 , 108 ]. Heldmann et al [ 109 ] found that white matter microstructural abnormalities were only detected in the left hemisphere in the PD risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Muzikos terapijos poveikis motorinei funcijai. Motoriniai sutrikimai sergant demencija pablogėja ligos metu, taip pat vystosi metais prieš bet kokį pažinimo sutrikimą [22]. Tačiau mažai ištyrinėtas MT poveikis motorinei funkcijai, sergant demencija.…”
unclassified